1983
DOI: 10.1128/iai.39.1.315-335.1983
|View full text |Cite
|
Sign up to set email alerts
|

Six widespread bacterial clones among Escherichia coli K1 isolates

Abstract: Variable properties among Escherichia coli isolates include serotype, electrophoretic migration of major outer membrane proteins, metabolic properties, production of hemolysin or colicin or both, and plasmid content. These characteristics were compared in E. coli strains of capsular types Kl, K5, K92, and K100 and in non-encapsulated isolates. The 234 bacterial strains from the United States and Europe which we studied had been isolated from healthy or diseased individuals recently or as long ago as 1941. Rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
200
3
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(214 citation statements)
references
References 34 publications
10
200
3
1
Order By: Relevance
“…Di¡erences with regard to the occurrence of some characteristics have already been observed. For example O'Brien et al demonstrated a large percentage of examined strains producing colicins (57.3%) [7] compared with isolates from Europe (21.6%) and the USA (33.3%) [23], while we have demonstrated 31% for strains from patients without infection and 44% for strains from intestinal infections.…”
Section: Discussioncontrasting
confidence: 44%
“…Di¡erences with regard to the occurrence of some characteristics have already been observed. For example O'Brien et al demonstrated a large percentage of examined strains producing colicins (57.3%) [7] compared with isolates from Europe (21.6%) and the USA (33.3%) [23], while we have demonstrated 31% for strains from patients without infection and 44% for strains from intestinal infections.…”
Section: Discussioncontrasting
confidence: 44%
“…OMP patterns have been shown to be closely associated with electrophoretic types and clones identified by MLEE in other species (Achtman et al, 1983;Musser et al, 1985Musser et al, , 1988Achtman and Pluschke, 1986;Kapur et al, 1992;Davies et al, 1997). The exclusive association of isolates of the less common capsular types with specific OMP-types provided evidence that OMP-types mark individual clonal groups of P. multocida (Achtman and Pluschke, 1986).…”
Section: Discussionmentioning
confidence: 95%
“…PII: S 0 3 7 8 -1 0 9 7 ( 0 1 ) 0 0 1 3 4 -3 S17-1 Vpir donor strain and tagged pUTmini-Tn5Km2 suicide vectors [1]. The E. coli K1 strains used in this study were RS218, serotype O18ac:K1:H7, a clinical isolate from a case of human newborn meningitis [7]; EV291, a spontaneous nalidixic acid-resistant derivative of RS218; and EV293, a spontaneous K1-speci¢c bacteriophage-resistant derivative of EV291 harboring a random insertion of a tagged mini-Tn5Km2 element. Loss of the EV293 capsule was con¢rmed by this strain's lack of reactivity against polysialic acid antibody [8].…”
Section: Methodsmentioning
confidence: 99%